Proceedings of the 2012 International Conference on Quantitative InfraRed Thermography 2012
DOI: 10.21611/qirt.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of heat generation sources in lock-in sonic thermography using laser Doppler vibrometry

Abstract: This study aims to investigate the fundamental physics governing the damping-related heat generation and thermal diffusion processes in ultrasound excited infrared thermography. Experimental tests were carried out on a AISI 304 steel beam in which an array of synthetic defects, consisting of 27 flat-bottom holes filled with a viscous material, has been manufactured. The relationship between vibration mode shape, ultrasound excitation frequency and energy dissipation in defective areas is examined by means of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
4
0
1
Order By: Relevance
“…Different excitation frequencies are studied, but only the results for a frequency of 5 kHz are reported here. This frequency is close to a resonant frequency of the samples that can guarantee the best results in terms of temperature variation as reported in [22,23,24]. Thermal images are acquired by an infrared camera (FLIR X6540) during 180 seconds at a 50 Hz frequency with an integration time of 3000 µs (to obtain the necessary resolution of above some tenths of a degree) [25].…”
Section: Experimental Approachmentioning
confidence: 91%
“…Different excitation frequencies are studied, but only the results for a frequency of 5 kHz are reported here. This frequency is close to a resonant frequency of the samples that can guarantee the best results in terms of temperature variation as reported in [22,23,24]. Thermal images are acquired by an infrared camera (FLIR X6540) during 180 seconds at a 50 Hz frequency with an integration time of 3000 µs (to obtain the necessary resolution of above some tenths of a degree) [25].…”
Section: Experimental Approachmentioning
confidence: 91%
“…Many researchers simply labeled heat generation in vibrothermography as friction induced, but other researchers suggested that thermo-plastic heat generation or thermoelasticity, viscoelasticity and anelasticity, or a combination of these mechanisms are the sources of crack heating [67]. For instance, Montanini et al stated that for flat-bottomed hole defects, viscoelasticity is the primary heat source, on the other hand the combination of viscoelasticity and friction is the primary heat source for elamination and cracks [68].…”
Section: Principle Of Heat Generation In Vibrothermographymentioning
confidence: 99%
“…These heat generation mechanisms may act individually or in combination. In the case of a flat-bottomed hole (FBH) defect, the primary heat source is viscoelasticity, whereas in delamination and cracks, the combination of both viscoelasticity and friction plays the main role [8,9]. Furthermore, a direct relationship between the excitation frequency and the generated heat on the cracks has been reported by Holland et al [10,11].…”
Section: Introductionmentioning
confidence: 99%